"Mise en Abyme" y parodia divezca en los epígrafes de The Buenos Aires Affair de Manuel Puig: Separación del amante. - Camacho Ramirez, Raimy (2012)
This article tries to demonstrate how, in the novel The Buenos Aires Affair by Manuel Puig, the epigraphs and the plot build a "mise en abyme" by means of the repetition of the "love scene" between the paratextual elements and the plot. This takes place both on the epigraphs, in the form of a classical film performance, and, in the parodic action of the characters Gladys Hebe Onofrio and Leopoldo Druskovitch. Mainly, the novel insists on the classical scene in romantic films, which is the encounter between beloved and lover.